2021
DOI: 10.1007/s00277-021-04617-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects between MPL and JAK2V617F on thrombosis and peripheral blood cell counts in patients with essential thrombocythemia: a meta-analysis

Abstract: To assess the effects between MPL and JAK2V617F on the thrombosis risk and peripheral blood cell counts in patients with essential thrombocythemia (ET), we identified eligible studies from PubMed, Embase, and the Cochrane Library. Seven studies were ultimately included in this meta-analysis. All studies reported the peripheral blood cell counts of ET patients, and three of them reported the eligible thrombotic events. In comparing the effect of MPL versus JAK2V617F on thrombosis, 1257 ET patients (73 MPL + and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…21 Moreover, over 60 years of age, smoking, the presence of JAK2 V617F mutation especially for ET and any history of thrombosis are considered the most important clinical risk factors for thromboembolic events in various publication and prognostic thrombosis risk scoring models such as International Prognostic Score for Thrombosis in ET (IPSET) and revised IPSET. [22][23][24][25][26][27][28][29][30][31] Additional risk factors for thrombosis include cardiovascular risk factors like hypertension, diabetes mellitus and male sex. 32,33 The results of our study are comparable with those classical concepts of CMPD.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…21 Moreover, over 60 years of age, smoking, the presence of JAK2 V617F mutation especially for ET and any history of thrombosis are considered the most important clinical risk factors for thromboembolic events in various publication and prognostic thrombosis risk scoring models such as International Prognostic Score for Thrombosis in ET (IPSET) and revised IPSET. [22][23][24][25][26][27][28][29][30][31] Additional risk factors for thrombosis include cardiovascular risk factors like hypertension, diabetes mellitus and male sex. 32,33 The results of our study are comparable with those classical concepts of CMPD.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Some authors have reported a higher probability of MF progression and death in MPL-mutated ET, whereas contradictory results have been reported regarding thrombosis. 7,22,[63][64][65] These discrepancies might be related to a confounding factor due to the older age of MPL-mutated patients. Moreover, a study including 1321 patients with ET characterized by next-generation sequencing (NGS) showed additional mutations in more than 50% of 60 cases, with MPL-mutated ET being the genotype with the highest proportion of additional mutations and clearly associated with older age.…”
Section: History Of Thrombosismentioning
confidence: 99%
“…determine treatment strategy. The CALR mutation is associated with a higher risk of haemorrhage rather than thrombosis, 7 and MPL mutations have been reported to be a risk factor for thrombosis 8,9 and progression to MF. 10 Moreover, genome-wide analyses have revealed that epigenetics and splicing-related non-driver gene mutations have a negative impact on the life expectancy of patients with myeloid malignancies, including primary MF, 11,12 which is one of the subgroups of MPNs.…”
Section: Impact Of Non-driver Gene Mutations On Thrombo-haemorrhagic ...mentioning
confidence: 99%
“…The presence of the JAK2 V617F mutation has been incorporated into thrombosis risk scoring systems, such as the International Prognostic Score for essential thrombocythemia (IPSET)‐thrombosis 4 and the revised IPSET‐thrombosis, 5,6 and these scoring systems are widely used to determine treatment strategy. The CALR mutation is associated with a higher risk of haemorrhage rather than thrombosis, 7 and MPL mutations have been reported to be a risk factor for thrombosis 8,9 and progression to MF 10 …”
Section: Introductionmentioning
confidence: 99%